Human papillomavirus infection and seroprevalence among female university students in Mexico - Alexander Pedroza-Gonzalez; Julia Reyes-Reali; Maricela Campos-Solorzano; Eloy Moises Blancas-Diaz; Janik Adriana Tomas-Morales; Aldo Aram Hernandez-Aparicio; Daniel Montes de Oca-Samperio; Efrain Garrido; Gina Stella Garcia-Romo; Claudia Fabiola Mendez-Catala; Patricia Alvarez Ortiz; Janet Sánchez Ramos; et al. (Taylor & Francis Group, 2022)
Human papillomavirus (HPV) is one of the most common causes of sexually transmitted diseases, and the main etiology of cervical cancer. This study was aimed to assess type-specific cervical HPV prevalence and their association with HPV-specific antibodies in a cohort of female university students. HPV genotyping was performed by amplifying and sequencing a fragment of the L1 protein. A BLAST search was performed to identify HPV types. HPV-specific IgG antibodies were measured by ELISA in serum samples. A total of 129 women participated, with an average age of 21.75 years. The prevalence of vaginal HPV infection was 74.42%. The most predominant high-risk HPV types were 18 (13.95%), 31 (10.85%), and 16 (9.3%). We found that early age at coitarche and a higher number of sexual partners were significantly associated with a high prevalence of HPV infection. In addition to sexual behavior, we observed that the presence of serum-specific IgG antibodies against HPV can impact the prevalence of the virus. Seropositivity to HPV-16 and HPV-18 was associated with a lower prevalence of HPV-16, but not for other HPV types. Of note, there was a lower proportion of HPV-specific seropositivity in women who had the presence of the same HPV type in a cervical specimen, suggesting an immunoregulatory mechanism associated with the viral infection. In conclusion, the prevalence of HPV in university women was higher than expected and it was associated with early age of sexual debut, an increasing number of sexual partners, and a low proportion of HPV seropositivity.